2018
DOI: 10.1186/s12913-018-3224-5
|View full text |Cite
|
Sign up to set email alerts
|

Setting a Nigeria national malaria operational research agenda: the process

Abstract: BackgroundEmploying malaria operational research (MOR) findings in planning national malaria control programmes is gaining increased attention. The malaria control foci are diverse, resources are limited; therefore, agreeing on priority areas is critical. Hitherto, the process of prioritising MOR questions in Nigeria has been limited to few stakeholders. In support of the National Malaria Elimination Programme’s (NMEP) effort at setting a MOR agenda, the Nigeria Field Epidemiology and Laboratory Training Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A low response rate of 13.32% was recorded in this study. This may be attributed to the use of a web-based questionnaire which is still a novel tool for data collection in Nigeria (Ajumobi et al, 2018). Although previous studies have demonstrated a lower response rate to a web-based questionnaire compared to a paper-based questionnaire (Ebert et al, 2018;Harrison et al, 2019); online data collection has been successfully used among university students in other countries with response rates as high as 90% (Mirón et al, 2019;Othman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A low response rate of 13.32% was recorded in this study. This may be attributed to the use of a web-based questionnaire which is still a novel tool for data collection in Nigeria (Ajumobi et al, 2018). Although previous studies have demonstrated a lower response rate to a web-based questionnaire compared to a paper-based questionnaire (Ebert et al, 2018;Harrison et al, 2019); online data collection has been successfully used among university students in other countries with response rates as high as 90% (Mirón et al, 2019;Othman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since scoping reviews can be an arduous, yet transparent method for mapping research areas, some recently used it as either a stand-alone or supplementary tool in agenda-setting in various fields in health research [6,7,8,9]. Montesanti et al used it as a sole tool in generating key research themes in primary health care in Canada to contribute to the efficient and equitable use of limited funding, and possibly reduced duplication [6].…”
Section: Introductionmentioning
confidence: 99%
“…Montesanti et al used it as a sole tool in generating key research themes in primary health care in Canada to contribute to the efficient and equitable use of limited funding, and possibly reduced duplication [6]. Alternatively, Ajumobi et al used a scoping review in developing introductory materials to guide the consultative process in setting Nigeria’s national malaria operational research agenda [7].…”
Section: Introductionmentioning
confidence: 99%
“…These sample have undergone similar entrepreneurship training which has been a national policy among tertiary institutions since the introduction “National Economic Empowerment and Development Strategy” (NEEDS) in 2004 for addressing the problems poverty, and unemployment generation and facilitate wealth creation and value re-orientation ( Agboola, 2010 ). Considering low responses rate of survey studies in Nigeria (see Ajumobi et al., 2018 ; Raimi et al., 2013 ), the increment of the sample by 30% (87) was considered giving a total of 378 questionnaires distributed to the sampled students.…”
Section: Methodsmentioning
confidence: 99%